Scientific Validation of Amalaki Rasayana through Pharmacognostic and Phytochemical Analysis (International Journal of Ayurveda and Pharma Research, 2025)
Classical Ayurveda textbooks explain numerous medicinal formulations that have been effectively utilized in wide range of therapeutic conditions. Rasayana is the branch of Ayurveda, focuses on rejuvenation, tissue regeneration, modulating immune system, and promoting healthy aging process. Amalaki rasayana (AR) is a Vayasthapana rasayana explained in Charaka samhitha. AR is extensively reported to influence various biological activities to promote longevity and prevent geriatric symptoms. Considering these factors, AR is planned to administer in age related cataract in its early stage. To improve the acceptance of medicinal preparations globally, it is necessary to revalidate them with the help of advanced scientific techniques, without losing the vital elements of science. Methods: The preparation was properly evaluated regarding safety, and quality. In the present study, pharmacognostical analysis of AR was done to ensure the quality standards of the raw drug and the finished product. Organoleptic character analysis, physiochemical analysis, heavy metal analysis, microbial analysis and HPTLC analysis were done. Result: Established standards were met in physicochemical, heavy metal and microbial analyses. These validate the formulation’s compliance with quality and safety requirements. HPTLC helped in detecting the marker compound gallic acid in the formulation. Conclusion: From the observations, the results of this study could serve as a baseline for future research works.